Role‐based Access Control Video Surveillance Mechanism Modeling in Smart Contract Environment. Issue 4 (14th February 2021) - Kim, Jinsu; Park, Namje
Abstract: Closed circuit television (CCTV) is installed on roads or in facilities for the purpose of filming videos to be used for crime prevention or as evidence for accidents in the future, and the number of CCTVs installed annually is increasing sharply. The videos collected by the devices can be submitted as legal evidence for accidents, which could happen in the future, but the damage to their integrity may cause the loss of reliability. Blockchain, which guarantees the integrity of data by sharing data as a distributed network method on these issues, can be applied as an effective means of data forgery. In general, however, video information contains sensitive data within the image, and sharing it externally can cause many problems. Thus, in this paper, by implementing role‐based approach control based on a block chain that guarantees integrity through sharing of data, a mechanism is proposed to share filmed images but prevent indiscriminate access by third parties. Abstract : In this paper, we proposed a video surveillance mechanism that can perform role‐based access control in a blockchain environment that provides smart contracts. Blockchain‐based mechanisms ensure the integrity of recorded data, and at the same time, by incorporating smart contracts, the reliability of the system administrator can be strengthened.